2019
DOI: 10.1111/pedi.12906
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to insulin therapy in youth with poorly‐controlled type 2 diabetes in the TODAY trial

Abstract: Objective To understand the factors associated with glycemic control after starting insulin in youth with type 2 diabetes following glycemic failure (persistent HbA1c ≥8%) with metformin alone, metformin + rosiglitazone or metformin + lifestyle in the TODAY study. Methods Change in HbA1c after add‐on insulin therapy and the factors predictive of glycemic response were evaluated. At 1‐year postinsulin initiation, 253 youth had a mean of 3.9 ± 1.0 visits since the time of insulin initiation. Participants were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…37,38 However, after TODAY subjects met criteria for insulin rescue, only 33% of the subjects achieved a HbA1c improvement of at least 0.5%. 39 It is unknown, whether medication non-adherence may contribute to the poor efficacy of insulin treatment. We posit that medication non-adherence may also explain the The TODAY study demonstrated that intensive lifestyle modifications mitigated weight gain in subjects on metformin monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 However, after TODAY subjects met criteria for insulin rescue, only 33% of the subjects achieved a HbA1c improvement of at least 0.5%. 39 It is unknown, whether medication non-adherence may contribute to the poor efficacy of insulin treatment. We posit that medication non-adherence may also explain the The TODAY study demonstrated that intensive lifestyle modifications mitigated weight gain in subjects on metformin monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The TODAY study showed that baseline beta‐cell function, and not medication adherence, is the dominant predictor for long‐term glycemic outcome 37,38 . However, after TODAY subjects met criteria for insulin rescue, only 33% of the subjects achieved a HbA1c improvement of at least 0.5% 39 . It is unknown, whether medication non‐adherence may contribute to the poor efficacy of insulin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Once participants reached the primary outcome in the TODAY study, metformin was continued, rosiglitazone (if present) discontinued and insulin initiated. Importantly, there was only a modest improvement in HbA 1c (<5.5 mmol/mol [<0.5%]) 6 months after insulin initiation, and no significant improvement in 1 year, such that mean HbA 1c was still 85.8 mmol/mol (10.0%) [25], highlighting the difficulty in achieving glycaemic control with only metformin and insulin once beta cell function has declined.…”
Section: What Do We Know About Treatment Effects From Current Studies?mentioning
confidence: 99%
“…In 2012, the TODAY study published the first trial comparing metformin alone, metformin plus an intensive lifestyle intervention, and metformin plus rosiglitazone, and only half of participants experienced durable glycemic control on metformin alone 15 . Of the adolescents with type 2 diabetes in the TODAY trial that failed oral antidiabetic treatment and were then started on insulin therapy, only 33% maintained a consistent reduction in HbA1c after 6 months of add‐on insulin therapy 18 . In the SEARCH study of youth with type 2 diabetes who were on metformin monotherapy at baseline, at mean follow‐up of 7 years, 27% had insulin added or switched to insulin alone 14 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Of the adolescents with type 2 diabetes in the TODAY trial that failed oral antidiabetic treatment and were then started on insulin therapy, only 33% maintained a consistent reduction in HbA1c after 6 months of add-on insulin therapy. 18 In the SEARCH study of youth with type 2 diabetes who were on metformin monotherapy at baseline, at mean follow-up of 7 years, 27% had insulin added or switched to insulin alone. 14 We similarly show high treatment failure rates in youth with type 2 diabetes who were initially successful in coming off insulin therapy yet could not sustain durable glycemic control on metformin or lifestyle alone, and ultimately, more than 50% of individuals required re-intensification of diabetes therapy.…”
Section: Discussionmentioning
confidence: 99%